2016
DOI: 10.1080/15569527.2016.1211670
|View full text |Cite
|
Sign up to set email alerts
|

A case of bullous pemphigoid ınduced by vildagliptin

Abstract: Bullous pemfigoid (BP), an autoimmune disorder, can also be induced by some medications. Vildagliptin is a new drug used to treat diabetes mellitus (DM). Recently, a few cases of vildagliptin-induced BP have been described in the literature. We report a patient with BP in which vildagliptin was thought to be as a possible causative agent. The awareness of BP development risk during gliptin therapy can prevent unnecessary usage of systemic drugs with serious side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 5 publications
0
13
0
3
Order By: Relevance
“…Although autoimmune bullous diseases are rare diseases with low annual incidences, among which BP is the least rare, associations have been published between drug intake and many BP ( 6 8 ) and LABD cases ( 50 ) but only a few MMPs ( 51 ). Since 2011, an increasing number of reports have suggested that gliptins trigger BP ( 9 15 , 17 23 ). Last, very recently, four comparative case–non-case studies demonstrated a significant association between gliptin intake and BP onset in diabetic patients ( 16 , 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although autoimmune bullous diseases are rare diseases with low annual incidences, among which BP is the least rare, associations have been published between drug intake and many BP ( 6 8 ) and LABD cases ( 50 ) but only a few MMPs ( 51 ). Since 2011, an increasing number of reports have suggested that gliptins trigger BP ( 9 15 , 17 23 ). Last, very recently, four comparative case–non-case studies demonstrated a significant association between gliptin intake and BP onset in diabetic patients ( 16 , 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Keseroglu et al [21] 61 F Vildagliptin/ metformin The duration of follow up not mentioned Aouidad et al [23] 61 M Vildagliptin/ metformin Pasmatzi et al [24] 59 F Vildagliptin/ metformin…”
Section: Still In Remission At 1-year Follow-upmentioning
confidence: 99%
“…The main cutaneous side effects reported with gliptins are cutaneous eruptions, pruritus, urticarial reactions, and some severe but rare reactions, such as toxic epidermal necrolysis or anaphylaxis (Andukuri et al, 2009;Banerji et al, 2010;Desai et al, 2010;Gerrald et al, 2012;Scheen et al, 2010). Forty-one case reports and small case series of gliptin-associated BP have been reported since 2011 (Aouidad et al, 2013;Attaway et al, 2014;Béné et al, 2015;Esposito et al, 2017;Fania et al, 2018;Garcia et al, 2016;Haber et al, 2016;Keseroglu et al, 2017;Mendonça et al, 2016;Pasmatzi et al, 2011;Sakai et al, 2017, Schaffer et al, 2017Skandalis et al, 2012;Yoshiji et al, 2018). Additionally, two case-non-case studies using pharmacovigilance databases reported a signal for an increased risk of BP during DPP-4 inhibitor exposure (Béné et al, 2016;Garcia et al, 2016).…”
Section: Introductionmentioning
confidence: 99%